Increase in insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein 1 after supplementation with selenium and coenzyme Q10. A prospective randomized double-blind placebo-controlled trial among elderly Swedish citizens. - Urban Alehagen; Peter Johansson; Jan Aaseth; Jan Alexander; Kerstin Brismar (PLoS ONE)
Background Insulin-like growth factor-1(IGF-1) has a multitude of effects besides cell growth and metabolism. Reports also indicate anti-inflammatory and antioxidative effects. The concentrations of IGF-1 decrease with age and during inflammation. As selenium and coenzyme Q10 are involved in both the antioxidative defense and the inflammatory response, the present study aimed to examine the effects of supplementation with selenium and coenzyme Q10 on concentrations of IGF-1 and its binding protein IGFBP-1 in a population showing reduced cardiovascular mortality following such supplementation. Methods 215 elderly individuals were included and given the intervention for four years. A clinical examination was performed and blood samples were taken at the start and after 48 months. Evaluations of IGF-1, the age adjusted IGF-1 SD score and IGFBP-1 were performed using group mean values, and repeated measures of variance. Findings After supplementation with selenium and coenzyme Q10, applying group mean evaluations, significantly higher IGF-1 and IGF-1 SD scores could be seen in the active treatment group, whereas a decrease in concentration could be seen of the same biomarkers in the placebo group. Applying the repeated measures of variance evaluations, the same significant increase in concentrations of IGF-1 (F = 68; P>0.0001), IGF-1 SD score (F = 29; P<0.0001) and of IGFBP-1 (F = 6.88; P = 0.009) could be seen, indicating the effect of selenium and coenzyme Q10 also on the expression of IGF-1 as one of the mechanistic effects of the intervention. Conclusion Supplementation with selenium and coenzyme Q10 over four years resulted in increased levels of IGF-1 and the postprandial IGFBP-1, and an increase in the age-corrected IGF-1 SD score, compared with placebo. The effects could be part of the mechanistic explanation behind the surprisingly positive clinical effects on cardiovascular morbidity and mortality reported earlier. However, as the effects of IGF-1 are complex, more research on the result of intervention with selenium and coenzyme Q10 is needed.